Regional urbanization and knowledge-intensive business activities (KIBS): an example of small and medium-sized cities in the Greater Stuttgart Region (Germany) - Wagner, Madeleine; Growe, Anna (Urban science, 2020)
The objective of this paper is to understand the role of small and medium-sized cities as economic locations, and as potential anchor locations, in grounding processes of regional urbanization in the knowledge economy. Based on quantitative occupational data, the deconcentration processes of knowledge-intensive business activities are analyzed for the Greater Stuttgart Region in southern Germany. The way in which the different knowledge bases used in knowledge-intensive business activities influence spatial patterns of economic activity in the surrounding area of the core city, including small and medium-sized towns, is discussed. The knowledge bases differentiated in this paper are analytical, synthetic and symbolic knowledge.